The neuroinflammation origin of autism spectrum disorder (ASD) – the literature review - Pytka, Michalina; Dalmata, Weronika; Należna, Paulina (Journal of Education, Health and Sport, 2025)
Introduction and state of the knowledge: The origin of neuroinflammation in autism spectrum disorder (ASD) remains unknown. The presence of immunological dysregulation in ASD is observed as abnormalities in lymphocytes subpopulations and alterations in pro-inflammatory cytokines' levels. Also kynurenine and histaminergic pathways are dysregulated, causing additional changes in the brain's structure and physiology. Inflammatory status include intestines as well the gut microbiota present characteristic features in ASD. Materials and methods: The literature search was done using PubMed database up, focusing on the newest knowledge concerning ASD. Aim: The aim of this review is to summarise the newest knowledge about molecular basis of neuroinflammation in ASD, to distinguish target molecules, that can predict autism's onset and to find dietary solutions, that can alleviate autistic behavioral features by tackling histaminergic and tryptophan pathways. Conclusion: Concerning chronic inflammatory state's presence in ASD, exact target molecules' levels can be checked in order to proove changes in immune system. To allieviate symptoms such as social cognition, meditherian diet, probiotics, magnesium, B vitamins and physical excercises are highly recommended.